Between community and contempt - Amanda Wilson (Canadian Food Studies, 2025)
This narrative piece presents eight vignettes from formerly incarcerated individuals, reflecting on their experiences of food and food provisioning within federal prisons in Canada. The stories and insights shed light on the negotiation and dynamic interplay between the imposition of unjust policies and the everyday creativity and persistence of those subject to its harmful carceral logic. In reading these vignettes we can also see how one might create greater moments of freedom and autonomy for incarcerated individuals, as part of a broader project of dismantling and re-imagining responses to harm and trauma.